Potency of aloe extract as immunostimulant for carp (Cyprinus carpio) against Aeromonas salmonicida - Sri Andayani; M. SULAIMAN DADIONO; WIDYA TRI ELWIRA; FEBBY HADI SETYAWAN (Society for Indonesian Biodiversity, 2020)
Abstract. Andayani S, Dadiono MS, Elwira WT, Setyawan FH. 2020. Potency of aloe extract as immunostimulant for carp (Cyprinus carpio) against Aeromonas salmonicida. Biodiversitas 21: 860-864. The objective of the study was to be able to know the cellular and humoral non-specific immune response to Aeromonas salmonicida after aloe extract administration. This study employed Complete Randomized Design with 3 treatments and 3 replications, control treatment (K), A =2 ppm of aloe extract application in the media, B = 16 ppm of aloe extract in the media, and C = 30 ppm of aloe extract in the media. The extract was given through one-hour soaking at day 0 and day 7, and then challenge-tested to 107 cells.ml-1 of A. salmonicida into the media for one day. Results showed that administration of aloe extract could raise plasma protein levels from 443.0 to 662.0 mg.Kg-1 antibody from 1.2576 to 3.3974, and phagocytic activity from 30.61% to 45.94%. Similarly, the differential value of leucocyte (lymphocyte from 58.6% to 73.70%, neutrophils from 6.09 to 8%, and monocyte from 5.70% to 7.72%). As conclusion, aloe extract at the dose of 2 ppm could raise the cellular and humoral non-specific immune. Therefore, the use of aloe extract as immunostimulant at the dose of 2 ppm applied through immersion could also apply other methods, such as oral and injection.